Role of reactive oxygen species in ultra-weak photon emission in biological systems - Pospíšil, Pavel; Prasad, Ankush; Rác, Marek (Journal of photochemistry and photobiology. B, Biology, 2014)
Ultra-weak photon emission originates from the relaxation of electronically excited species formed in the biological systems such as microorganisms, plants and animals including humans. Electronically excited species are formed during the oxidative metabolic processes and the oxidative stress reactions that are associated with the production of reactive oxygen species (ROS). The review attempts to overview experimental evidence on the involvement of superoxide anion radical, hydrogen peroxide, hydroxyl radical and singlet oxygen in both the spontaneous and the stress-induced ultra-weak photon emission. The oxidation of biomolecules comprising either the hydrogen abstraction by superoxide anion and hydroxyl radicals or the cycloaddition of singlet oxygen initiate a cascade of oxidative reactions that lead to the formation of electronically excited species such as triplet excited carbonyl, excited pigments and singlet oxygen. The photon emission of these electronically excited species is in the following regions of the spectrum (1) triplet excited carbonyl in the near UVA and blue-green areas (350-550nm), (2) singlet and triplet excited pigments in the green-red (550-750nm) and red-near IR (750-1000nm) areas, respectively and (3) singlet oxygen in the red (634 and 703nm) and near IR (1270nm) areas. The understanding of the role of ROS in photon emission allows us to use the spontaneous and stress-induced ultra-weak photon emission as a non-invasive tool for monitoring of the oxidative metabolic processes and the oxidative stress reactions in biological systems in vivo, respectively.
Keywords: Reactive Oxygen Species; fotobiologie; Humans; oxidace-redukce; zvířata; Photobiology; Electrons; Animals; reaktivní formy kyslíku; Oxidation-Reduction; lidé; fotony; elektrony; Photons